Physiological Responses of Bali Cattle Associated with Temperature-Humidity Index under Tropical Environmental Conditions - Kirana Dara Dinanti Adiputra; Sukandi; Cori Qamara; Novemia Fatmarischa; I Putu Gede Didik Widiarta (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2025)
The temperature-humidity index (THI) is an indicator that combines air temperature and humidity to assess the level of comfort or heat stress in livestock. This study aims to evaluate the relationship between the physiological response of Bali cattle to THI in tropical areas. A total of 20 Bali cattle (10 males and 10 females) were observed in the morning and afternoon. Microclimatic data (temperature, humidity, THI) and physiological responses, including rectal temperature (RT), skin surface temperature (ST), respiratory rate (RR), and heart rate (HR), were analysed using the General Linear Model (GLM) with repeated measures and linear regression. The results showed significant differences (P<0.01) between morning and afternoon. THI increased from 77.34 ± 0.82 (mild heat stress) in the morning to 86.04 ± 1.20 (severe heat stress) in the afternoon. Physiological responses increased significantly in the afternoon, with males showing higher RT and RR than females. Regression analysis indicated that THI was closely related to RT (R² = 0.8822), RR (R² = 0.8065), and HR (R² = 0.9454), while ST showed a moderate relationship (R² = 0.5503). It can be concluded that Bali cattle are sensitive to tropical climate fluctuations, and THI can be used as an indicator to assess heat stress levels in Bali cattle.